Age, executive functioning, and decision-making styles in adults: a moderated mediation model. Issue 3 (3rd May 2020) - Fatima, Shameem; Khan, Manoor; Rosselli, Monica; Ardila, Alfredo
ABSTRACT: The current study aimed to assess: i) whether executive functioning (EF) mediates the association of age with different decision-making (DM) styles in adults, and ii) whether these mediational associations change with age in adulthood. Our sample included 195 adults (110 young adults and 85 middle-aged adults; 95 males) selected from different government, semi-government, and private sector organizations. They were assessed on a self-report measure of General Decision-making Styles and on two EF tests: the Design Fluency Test and the Color-Word Interference Test from the Delis–Kaplan Executive Functions System. Results indicated that EF mediated the association of age with three decision-making styles including dependent, avoidant, and spontaneous DM. However, a conditional indirect effect of EF was significant only for spontaneous DM, indicating stronger indirect effects for middle-aged adults than for young adults. The findings highlight the idea that EF is an important factor in DM, particularly during middle adulthood.